CITOTOXICITY TEST OF THE PROTEIN FRACTIONS OF CARICA PAPAYA L. LEAVES ON HeLa CELL LINE. - Rumiyati .; Sismindari .; Sudjadi . (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2003)
Previous research showed that a RIP like protein from Carica papaya L. leaves was available on 60 – 80% saturation ammonium sulfate fraction. In this research cytotoxicity assay of the protein fractions was carried out on HeLa cell lines.RIP-like protein from Carica papaya L. leaves, isolated leg ammonium sulfat saturation was prepared based on the ability of cleaving double stranded supercoiled DNA. This fraction was then tested its cytotoxicity on HeLa cell lines.The results indicated that fraction at 60% and 80% saturation possessed lower activity with the LC50 of 1,35 mg/ml and 0,936 mg/ml, respectively compared to the crude extracts (LC50 0,623 mg/ml). The higher toxicity level of the crude extract might be caused also by toxicity of other compounds containing in the crude extract.Key word : cytotoxicity, protein fraction, HeLa cell line